An Evaluation of Forced Distance Learning and Teaching Under Pandemic Conditions Using the Technology Acceptance Model - Drueke, Barbara; Mainz, Verena; Lemos, Martin; Wirtz, Markus Antonius; Boecker, Maren (Frontiers in Psychology, 2021)
Research: Due to the sudden outbreak of Covid-19 and the resulting pandemic situation universities were forced to rapidly change their traditional pedagogical and didactical approach by shifting from mostly face-to-face teaching entirely to virtual and online teaching methods. Through this, a ‘forced’ distance learning and -teaching situation emerged. This study aimed at investigating the effect of these innovations on the implementation, acceptance and use of the virtual teaching offer within the framework of the technology acceptance model (TAM). Methods: A total of 218 students and 69 lecturers of a German Medical Faculty completed online questionnaires on the acceptance, satisfaction and usefulness of the forced distance learning (FDL) and teaching (FDT), respectively. An extended version of the TAM was used to assess students’ and lecturers’ acceptance of FDL and FDT. In order to estimate the multivariate dependencies, path analysis was employed using structural equation modeling (SEM). Results: In general, students and lecturers reported to be satisfied with the implementation of the FDL and FDT. Regarding the TAM model, the fit indices suggested an acceptable model fit for both groups. The students’ model revealed that the perceived usefulness had a strong predictive power on the attitude towards using and the perceived ease of use also predicted the attitude. The existing technical infrastructure as well as the general media affinity and pandemic related worries proved to be positively associated with the perceived usefulness while data security worries and organization of online teaching predicted the perceived ease of use in students. The strong positive predictive power of the perceived usefulness for the attitude towards using was also evident in the model for the lecturers and the technical infrastructure predicted the perceived the perceived ease of use in the lecturers. Conclusion: The TAM is a suitable framework to represent the implementation, acceptance and use of the virtual teaching offer during the special pandemic situation at the university. However, personal and structural context factors were important predictors for the perceived usefulness and the perceived ease of use in the student group.